2002
DOI: 10.1029/2001jc000831
|View full text |Cite
|
Sign up to set email alerts
|

Observations of barrier layer formation in the Bay of Bengal during summer monsoon

Abstract: Time series of temperature and salinity in the upper ocean, measured at 17°30′N, 89°E in the northern Bay of Bengal, from 27 July to 6 August 1999 captured an event of upper layer freshening. Initially, the upper layer that is homogeneous in both temperature and salinity was about 30 m deep. Subsequently, the arrival of a freshwater plume caused the depth of the mixed layer to decrease to about 10 m and the salinity in the surface layer by about 4 psu. The plume led to the formation of a new halocline and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
227
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(241 citation statements)
references
References 22 publications
13
227
0
1
Order By: Relevance
“…High SST in the BoB is conducive to deep convection in the atmosphere and hence precipitation during the SW monsoon season (Gadgil et al 1984;Shenoi et al 2002). Altered atmospheric convection results in variations in air-sea heat flux, which can further influence the convection itself via SST changes (Krishnamurti et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High SST in the BoB is conducive to deep convection in the atmosphere and hence precipitation during the SW monsoon season (Gadgil et al 1984;Shenoi et al 2002). Altered atmospheric convection results in variations in air-sea heat flux, which can further influence the convection itself via SST changes (Krishnamurti et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The unique summertime and wintertime oceanic conditions associated with the presence of a low-salinity layer lead to marked variations in density stratification and vertical mixing in the BoB both in summer (Vinayachandran et al 2002) and winter (Shetye et al 1996). The strong halocline associated with the surface freshwater cap shoals the density mixed layer (ML), while the isothermal layer depth (ILD) is usually deeper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of fresh water leads to salt-stratified upper-ocean water column and the formation of a barrier layer (BL), a layer sandwiched between the bottom of the mixed layer (ML) and the top of the thermocline, in the BoB (Lukas and Lindstrom, 1991;Vinayachandran et al, 2002;Thadathil et al, 2007). The BL restricts the entrainment of colder waters from thermocline region into the mixed layer; it thereby maintains a warmer ML and sea surface temperature (SST).…”
Section: Introductionmentioning
confidence: 99%
“…Two cells of very low density are found off the central east coast of India and northwest of the Andaman Islands, where freshwater discharges from the Krishna and Irrawady Rivers, respectively, enter the Bay [4] . Work has already been done on the entire oceans on geostrophic current using altimetry data and in the Indian Ocean [5][6][7][8] . During the 2004 tsunami, research on a satellite view of internal wave [9] found the effect of tsunami on marine ecosystem [1] .…”
Section: Densitymentioning
confidence: 99%